Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (De Boeck Supérieur, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."–Quatrième de couverture.
Section: xxi, 326 pages : illustrations ; 24 cm.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences